Peranan Media Pengajaran dalam Pembelajaran Bahasa - Sofia, Sofia (Al-Hikmah, 2012)
Teaching language is like the adults (father-mother) teach their baby to practice speaking. Naturally, a child or a baby just imitates or repeat what the adults say. However, to accelerate and to grow up their skill in uttering the word media is needed, because it has function to make something abstract to be real and concret, as well as, to ease baby or children understand what they hear. Such this case accure in teaching and learning process where media is treated as a means of transferring knowledge. Good media leads a teacher or lecturer to good educative interactions in which it could strengthen the method of learning